Vulnerabilidade de reservatórios em rios de alta variabilidade em um cenário de mudanças climáticas - Cysne, Andréa Pereira (2007)
It is much talked nowadays about the possible climatic changes as a result of the gas emission on the atmosphere. Although it is not a common agreement, a great part of the scientific community believe that an elevation of the measured global temperature will occur, which can provoke, for example, a medium increase on the ocean levels. Associated to this, there is also a consensus that significant transformations will happen on the pluvial and evaporation regimen around the world. However, the quantification of these changes, on specific locations, is still needed more studies, which can allow more conclusive evaluations about the theme. With that been said, this study tried to put some light on this theme, and considering some scenarios of alteration on the precipitation patterns and evaporation (considering liquid evaporation = E-P) it was evaluated the impact of these climatic changes in reservoirs yield at Northeast Semi-Arid of Brazil. whose rivers present high coefficient of variation of the annual emanations. It was observed that in rivers less variable – CV equal to 0,6 and 0,8 – it is necessary that the net evaporation EL increase 60% so that the reservoir can lose about 10% of its regularized outflow. But for rivers with high variability – CV equal to 1,4 and 1,6 – the net evaporation – would need a increase of just 30% so that the reservoir could be the object of the same reduction. It was concluded that, as most of the half-barren northeast’s reservoirs are located on rivers that present variation coefficients of the annual emanations in lathe of 1,2 to 1,6 , a greater attention should be given to these, since it showed sensible enough to the climatic variations.